Reading promotion on social digital networks through infographics: The strategy of the government of Mexico, 2019-2023 - Rivera Salas, Paola Eunice (European Public & Social Innovation Review, 2025)
Introduction: Promoting reading through digital environments is a relevant strategy given the need to increase the population's development level. Methodology: Descriptive, transversal, non-experimental through a quantitative content analysis technique of 577 infographics published on Facebook. Results: 50% of the infographics are aimed at new readers. Likewise, the youth population is the public that is served the most. In addition, significant interaction is generated with netizens in collaborative environments. Discussions: Infographics support persuading audiences to consume scientific and literary texts in social digital networks. The elements of these visual formats, such as images and units of information, are attractive and interesting for readers. Conclusions: It is essential to continue with digital formats, such as infographics, to increase the possibilities of promoting the reader to new audiences and to help strengthen the population's culture.